Characterization of Plant Small RNAs by Next Generation Sequencing. Issue 1 (3rd March 2017) - Mathioni, Sandra M.; Kakrana, Atul; Meyers, Blake C.
Abstract: Plant small RNAs are ∼20 to 24 nucleotide noncoding RNAs that typically have repressive regulatory roles in gene expression, functioning at the transcriptional or post‐transcriptional level. This influence on regulation of developmental and physiological processes has direct effects on phenotype. High‐throughput sequencing technologies have enabled the sequencing of millions of small RNAs. Along with decreased sequencing costs, recent improvements in small RNA library construction have facilitated the ability to use minimal amounts of input RNA for analysis. This unit describes steps to isolate total RNA from limited amounts of plant tissue to construct small RNA libraries and perform small RNA data processing. © 2017 by John Wiley & Sons, Inc.